A geographical information system (GIS) as an innovative approach for preserving vernacular architectural heritage - Rohayu Daud; Ab. Aziz Shuaib (Universiti Malaysia Kelantan, 2015)
This research practically investigates on how to manage and preserve valuable vernacular houses by using Geographical Information System (GIS) as an effective technological approach towards architectural preservation in Malaysia. The study explores a system correlates to create a new and innovative trend and to enhance building preservation which is frequently applied in geograph- ically oriented network computer technology. For the purposes of discovery, invention, and creation approach, data were collected using qualitative method followed by visual analytical matrix in vernacular houses; and thus, traditional houses in Kelantan have been identified, characterized and catalogued. The collaboration between architectural and GIS produces a more creative technique towards impact studies. By preserving and documenting the heritage values in the history of architecture and related bodies, it could inject more innovative paradigm in recognizing the cultural heritage that is valuable enough.